Room-temperature plasticity and size-dependent mechanical responses in small-scale B1-NbC(001) single-crystals. (December 2021) - Aleman, A.; Zaid, H.; Cruz, B.M.; Tanaka, K.; Yang, J.-M.; Kindlund, H.; Kodambaka, S.
Abstract: We report on the mechanical responses of NbC(001) single-crystals subjected to nanoindentation and in situ scanning electron microscopy based uniaxial microcompression tests at room-temperature. Using X-ray diffraction and X-ray photoelectron spectroscopy, we determine that the as-purchased bulk NbC is a 001-oriented, B1-structured, single-crystal with lattice parameter of 0.4446 ± 0.0002 nm and C/Nb ratio of ∼0.99. From nanoindentation experiments performed on the bulk crystal using a Berkovich diamond indenter, we measure an elastic modulus of 495 ± 14 GPa and an indentation-depth ( h ) dependent hardness decreasing from 31.0 ± 1.2 GPa at h  = 0.2 µm to 26.4 ± 0.4 GPa at h  = 0.9 µm. During uniaxial compression of cylindrical pillars with top diameters D between ∼0.25 µm and ∼0.75 µm, we observe strain hardening, increasing yield strengths with decreasing D, and surprisingly extensive plastic deformation with strains exceeding 2% and up to 30% in larger-size pillars. Electron microscopy characterization of the compressed pillars reveal slip traces characteristic of {110}〈1 1 ¯ 0〉 and {111}〈1 1 ¯ 0〉 slip systems. We suggest that the unexpected activation of {111}〈1 1 ¯ 0〉 facilitates plasticity in NbC(001). Graphical abstract: Image, graphical abstract